The Institutional Presidency from a Comparative Perspective: Argentina and Brazil since the 1980s - Magna Inácio; Mariana Llanos (German Institute of Global and Area Studies (GIGA), 2014)
This paper focuses on the evolution of the institutional presidency - meaning the cluster of agencies that directly support the chief of the executive - in Argentina and Brazil since their redemocratization in the 1980s. It investigates what explains the changes that have come about regarding the size of the institutional presidency and the types of agency that form it. Following the specialized literature, we argue that the growth of the institutional presidency is connected to developments occurring in the larger political system - that is, to the political challenges that the various presidents of the two countries have faced. Presidents adjust the format and mandate of the different agencies under their authority so as to better manage their relations with the political environment. In particular, we argue that the type of government (coalition or single-party) has had consequences for the structure of the presidency or, in other words, that different cabinet structures pose different challenges to presidents. This factor has not played a significant role in presidency-related studies until now, which have hitherto mostly been based on the case of the United States. Our empirical references, the presidencies of Argentina and Brazil, and typical cases of coalitional as well as single-party presidentialism respectively all allow us to show the impact of the type of government on the number and type of presidential agencies.
Keywords: 300; Argentina; Brazil; institutional presidency; presidential office; coalition presidentialism; comparative political institutions